Degrees of democraticity - Lars Bergström (Oñati Socio-Legal Series)
People have tended to load their different conceptions of democracy with their own political ideals; in this paper it is argued that normative and definitional questions should rather be separated, so that political philosophers and political scientists may adopt the same concept of democracy, even if they disagree normatively or politically. Moreover, it is argued that we should replace an absolute notion of democracy by a relativized notion, which allows for different degrees of democraticity. This facilitates the separation of normative and conceptual issues and it is convenient in contexts in which “democratic deficits” are discussed – as e.g. when democracy is to be implemented on a supranational level. Moreover, it has the consequence that democratic deficits are not necessarily bad.